PENGEMBANGAN APLIKASI DAN PELATIHAN WHATSAPP BROADCASTER DI LEMBAGA KURSUS ABC CALISTUNG - Luqman Affandi; Ade Ismail; Rokhimatul Wakhidah; Arwin Datumaya Wahyudi Sumari; Dhebys Suryani Hormansyah (Jurnal Pengabdian kepada Masyarakat, 2023)
Implementation of Community Service activities with the title "Development of Whatsapp Broadcaster Applications and Training at the ABC Calistung Sidoarjo Course Institute" was carried out on March 1, 2021 to October 31, 2021. Meanwhile, the implementation of applications, training and mentoring was carried out online on July 27, 2021 The results that have been achieved in the implementation of this PkM are Services in the form of training and assistance in using the Whatsapp Broadcaster application, the product is in the form of the Whatsapp Broadcaster application that has been installed on partner servers, intellectual Property Rights in the form of Copyrights that are still in the form of a submission draft.